2007
DOI: 10.1093/jpepsy/jsm093
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Special Issue: Journal of Pediatric Psychology Statement of Purpose—Special Section on Diversity and Health Care Disparities

Abstract: Data from the 2000 census reveal that the United States is becoming increasingly diverse at a rapid pace. Between 1990 and 2000, the Latino/Hispanic population increased by >50% (Guzmán, 2001), and the Black and Asian populations both increased at faster rates than the total population (Barnes & Bennett, 2002; McKinnon, 2001). Population projections indicate that between 2000 and 2010, the proportion of individuals considered ''White alone (not Hispanic),'' will decrease from 69.4% to 65.1%, and by 2050 will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Health disparities are defined as differences between demographic groups in the overall rate of disease incidence, prevalence, morbidity, mortality, or survival (McQuaid, 2008). Health disparities are defined as differences between demographic groups in the overall rate of disease incidence, prevalence, morbidity, mortality, or survival (McQuaid, 2008).…”
Section: Effect Of Social Determinants On Asthma: a Developmental Biomentioning
confidence: 99%
See 1 more Smart Citation
“…Health disparities are defined as differences between demographic groups in the overall rate of disease incidence, prevalence, morbidity, mortality, or survival (McQuaid, 2008). Health disparities are defined as differences between demographic groups in the overall rate of disease incidence, prevalence, morbidity, mortality, or survival (McQuaid, 2008).…”
Section: Effect Of Social Determinants On Asthma: a Developmental Biomentioning
confidence: 99%
“…There is abundant evidence that health disparities are due to multiple factors, many of which are social and emotional stressors, as well as factors that interfere with access to health care and disease management. Health disparities are defined as differences between demographic groups in the overall rate of disease incidence, prevalence, morbidity, mortality, or survival (McQuaid, 2008). Low socioeconomic minority children experience differentially high morbidity and mortality from asthma (Bender, Milgrom, Rand, & Ackerson, 1998;Celano et al, 2010;McQuaid, Walders, Kopel, Fritz, & Klinnert, 2005).…”
Section: Effect Of Social Determinants On Asthma: a Developmental Biomentioning
confidence: 99%
“…Ultimately, this special issue is about leveraging the power of research to promote and inform actions to address disparities and inequities in pediatric populations and in the practice of pediatric psychology. To move the health disparities research agenda forward, the Journal of Pediatric Psychology ( JPP ) has previously published special issues on economic, health, and mental health disparities among ethnic minority children and families ( Willis, 2002 ); advancing research on the intersection of families, culture, and health outcomes ( McQuaid & Barakat, 2012 ); and diversity and health disparities ( Lescano et al., 2016 ); as well as a special JPP section on Diversity and Health Disparities ( McQuaid, 2008 ). Each of these efforts has resulted in a broader array of publications focused on pediatric health disparities; but, now is the time to systematically advance the pediatric health disparities research agenda.…”
mentioning
confidence: 99%
“…Despite the growing Latino population in the United States and continued calls to consider culture in medical settings, few studies address the role of culture in pediatric medical care (Committee on Pediatric Workforce, 2004) or pediatric psychology (Clay, Mordhorst, & Lehn, 2002;McQuaid, 2008). Within pediatric oncology, a recent review of how culture influences family management of childhood cancer found that only 1 out of the 19 studies reported on Latino families (Gustafson Thibodeaux & Deatrick, 2007).…”
mentioning
confidence: 99%